Arranjos produtivos globalizados: o caso do APL da fruticultura de melão de Mossoró - Baraúna-RN - Oliveira, Estevani Pereira de (2011)
This study discuss the issue on Clusters Global, the productive arrangement of fruits melon Mossoró/Baraúna in Rio Grande do Norte, located in the Potiguar semi-arid RN, is entered in the arket international level, the job serch, from the benchmark neo-schumpeterian, strongly condensed and absorbed in Brazil by focusing on Local Productive Arrangements set out by the Reseatch Netwoark on Sistemas Produtivos e Inovativos Locais (REDESIST), understanding the extent to which innovation efforts, and as interactions between the main actors that make up this APL in particular, account for its global insertion. The methodology includes the application of questions to the producers of melon arrangement as well as interviews with the main responsible for the support, promotion and financing. In conclusion, there is a significant interaction between producres and actors of the arrangement, a fact that contributes to the integration into the international market together with the implementation of relevant innovations. Finally, it is pointed out the need for public policies directed to the production of melon because of its relevance to the exports of Rio Grande do Norte